BIBLIOMETRIC ANALYSIS: E-BOOK AND READING COMPREHENSION IN EFL IN THE LAST DECADE - Afifa Meitifazahra; Maman Suryaman; Kelik Wachyudi (STKIP PGRI Situbondo, 2023)
This study examined the analysis of e-books and reading comprehension in EFL in the last ten years. Academics have teaching-learning procedures. In learning one of the skills required in education is reading. Reading is necessary for students' personal and academic development, and reading comprehension is also essential. Reading comprehension is a student's understanding of a text's meaning and value. One learning media that may increase students' reading comprehension in the classroom is the e-book. An E-book is an electronic version of a printed book. The study employs bibliometrics to assess a research trend. This analysis utilizes Scopus information from 2012 to 2022 using PoP, VosViewer examines the metadata, and Tableau Public visualizes the VosViewer findings. This analysis reveals publishing trends, most cited authors and articles, journal rank, publication categories, article pages, nations, and keywords. This study discovered that the map from 29 datasets has 117 terms and 85 items, 13 clusters, and 263 links with 265 link strengths. Some keywords have big circles, such as